A Framework for Archaeological Involvement with Human Genetic Data for European Prehistory - Sørensen Marie Louise Stig; Hofmann Daniela; Kristiansen Kristian; Demeter Fabrice; Nielsen Rasmus; Willerslev Eske (Open Archaeology)
A concern with ethics and commitments to ethical conduct and standards has increasingly been raised within archaeology, recently also concerning aDNA data. We suggest that codes, whether for working with ancient DNA or other archaeological practices, need to be multi-faceted, or layered, to reflect the different situational contexts of research. We further argue for a more reflexive text addressing “issues of attention” or “concerns.” We address a number of concerns that should be considered and balanced against each other in the research process. They include respect, rights, appropriation, access, and collaboration.